Assessing coaches` professional knowledge: Test construction and field study based on the German Football Association`s Junior Coach training programme - Heim, C.; Ennigkeit, F.; Ullrich, M. (German Journal of Exercise and Sport Research, 2018)
Professional competency of sport and exercise coaches has been conceptualised differently depending on the theoretical and methodical approach taken. To date, no model of professional coaching competency has been agreed upon. The aim of this study was to develop a competency model for sport coaches drawing on well-known competency models developed in the context of teacher education and to empirically assess parts of the model. We developed an initial pool of 295 multiple choice items and administered them to a sample of 531 youths (mean age: 16.2 years) directly after they had completed the German Football Association`s (Deutscher Fußball-Bund) "Junior Coach in Schule und Verein" (Junior Coach for Schools and Clubs) training programme. Results of analyses of one-, two-, five-, and six-dimensional models by means of Rasch scaling indicate that the data are best represented by either a two- or a five-dimensional model depending on the fit criteria chosen. While content knowledge and pedagogical content knowledge are presented in the two-dimensional model, the five-dimensional model allows discrimination among football-specific content knowledge, basic content knowledge of training science, basic content knowledge of first aid and pedagogical content knowledge of planning training sessions and instructional/methodological pedagogical knowledge. Further investigation should be made into the suitability of competency models developed in the context of teacher evaluation for modelling the competency of sport coaches and into the extent to which such models can be extrapolated to various sports.